Creative Teaching Method in Higher Education for Industrial Design Programme - Pei Kian, Teo; Kamin, Yusri; Sukri Saud, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the criteria for emphasizing creative teaching methods in design education specializing in the program of industrial design. Creative teaching in educational fields is a must in today’s extremely competitive world, particularly in design education. Teaching and learning for a new era, especially design programs, requires a new model of education as design technology changes every year. This means that design education strategy needs a set of teaching methods that influence innovative development. In this manner, the content explores to assimilate the theories, strategies, techniques, and platforms of both innovative and mixed teaching, including the use of lively, transferable skills and computer software. A set of teaching techniques and strategies were applied to guide industrial design educators through problem-solving in teaching design and the implementation of new ideas. It is hoped that creative teaching can improve learning effectiveness and help to achieve teaching goals. The objectives of this article are to create a concept of creative teaching methods for an industrial design program, to identify techniques and strategies for creative teaching methods that provide students with a good outcome, and to explore how processes of creative teaching methods in industrial design programs work. This article compiles secondary data on a topic by accredited scholars and researchers, critically reviews existing research on the topic, and analyzes contrasting perspectives and theoretical approaches. This article uses meta-analysis to indicate the strength of variable relationships for creative teaching methods for an industrial design program, including the definition of industrial design, learning theories, creative techniques, creative platforms, and creative teaching methods in common practices. In summary, this paper consolidates the concept of teaching methods for industrial design programs and the importance of creative elements in a higher education setting.